Antibacterial activities of culturable actinomycete isolates collected from soils of the Langun-Gobingob cave complex in Calbiga, Samar. - Damayo, Jeffrae Isaac Albert R. (Jeffrae Isaac Albert R. Damayo, 2019)
The rise of antibiotic resistant bacteria threatens the potency of common antimicrobial products. This challenge to known antibiotics has reignited the search for novel bioactive compounds. The discovery of rare Actinomycetes from unexplored areas has proved to be a promising source of new antimicrobials. The Langun-Gobingob cave complex in Calbiga, Samar is the second largest cave complex in Asia, yet this is the first search for actinomycetes conducted in the area. The main objective of this study was to assess the antibacterial activities of culturable actinomycetes from soil samples from the Langun-Gobingob cave complex. Five actinomycete colonies were isolated in pure culture from soil samples using Starch-Casein Agar medium. The isolates were identified by their morphological characteristics and they were characterized by 16S rRNA sequencing. The sequences were matched to sequences uploaded to the NCBI Basic Local Alignment Search Tool (BLAST). Four of the isolates belonged to the Genus Streptomyces and one belonged to the Genus Nocardia. The antibacterial properties of the isolates were tested against gram-positive and gram-negative bacteria. One Streptmyces isolate exhibited antibacterial activity against the two gram-positive test bacteria. The limited area covered by the study leaves the cave complex mostly unexplored in the search for antibacterial secondary metabolites.